Influence of calcination temperature on the physicochemical properties of atomic/molecular layer deposited hybrid inorganic/organic ceramic nanofiltration membranes - M.P. Nijboer; H. Sondhi; E. Makhoul; M. Bechelany; S. Gabrielli; F. Roozeboom; A. Nijmeijer; A.Y. Kovalgin; M.W.J. Luiten-Olieman (Open Ceramics)
Post-deposition calcination in the air of hybrid inorganic/organic layers is considered to remove the organic constituents and completely create a full inorganic membrane. This study aims to investigate to what extent such a removal occurs and the effect of remaining organic constituents on the physicochemical properties of the membrane layer.Three hybrid layers were deposited using trimethylaluminum, two aliphatic- (ethylene glycol and 1,6-hexanediol) and one aromatic alcohol (hydroquinone). The effects of the different calcination treatments on the physicochemical properties were investigated. Differential thermogravimetric analysis established that the maximum mass loss rate temperatures for the hybrid layers grown from the aliphatic alcohols are lower than those from the aromatic co-reactant. After 250 °C, water contact angles (WCAs) were between 46° - 92° and IR spectroscopy and XPS showed the presence of carbon. Calcination at 350 °C reduced the WCA to 0° - 25° and decreased carbon content.